The Effectiveness of English Debating In Teaching Speaking For Senior High School Students - Ismail Ismail; Rusdin Rusdin (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2023)
The aim of this study is to find out the effect of using debating toward students’ motivation to speak English. The populations of this study were the second year students of MAN Dompu consists of 7 classes so the total number of them is 193. To facilitate it, the researchers used random sampling consisting of 32 students. They were divided in two groups namely experimental and control group, to collect the data the researcher used two tests they were pre-test and post-test, the researcher gave different treatment for experimental and control group. From the result of the test, it can be seen that the mean score of experimental was (24.36) is higher than the control group (15.96). Then it was continued to analyze both mean score by using t-test. The result shows that t-test is (1.63), the computation of correlation between the mean scores of the groups has a result of (8.40). Based on the result of the data analysis the alternative hypothesis which said that “The English debating has positive effect in teaching speaking of the second year students of MAN Dompu” is accepted, and the null hypothesis which is said, “The debating has not positive effect in teaching speaking of the second year students MAN Dompu” is rejected. This study quantitatively investigated the effectiveness of English debating program in teaching English. Similar studies which qualitatively explore English debating in teaching English are highly recommended